Pengaruh Pelayanan Pasien di Poli Pedodontik Integrasi Terhadap Kepuasan Pelayanan - Linda, Leo; Tullah, Muh. Firdaus; Maulida, Safira Nurul; Yuniar, Ainun Ayu (Poltekkes Kemenkes Bandung, 2025)
This study is based on the importance of service quality as a primary factor in determining patient satisfaction, particularly in pediatric dental care.This study aimed to determine the effect of patient services in the Integrated Pedodontics Clinic on patient satisfaction at the Hasanuddin University Dental and Oral Teaching Hospital (RSGMP). This study used a quantitative approach method with a cross-sectional design and data collection techniques through questionnaires distributed to 60 parents of patients at the Integrated Pedodontic Polytechnic of RSGMP Unhas. The selected respondents used incidental sampling techniques. The research was carried out in July–August 2025. Data were analyzed using simple linear regression using SPSS. The results of the study indicate that patient care has a positive and significant influence on service satisfaction, with a significance value of 0.000 (<0.05) and a coefficient of determination (R²) of 0.480, meaning that 48% of the variation in service satisfaction is influenced by the quality of patient care. Thus, the better the service provided in the pedodontics clinic, the higher the level of patient satisfaction.